Acquired Haemophilia A Associated with Subsequent Hepatocellular Carcinoma - Pacholczak, Renata; Bazan-Socha, Stanisława; Zdziarska, Joanna; Iwaniec, Teresa; Walocha, Jerzy A.; Musiał, Jacek; Dropiński, Jerzy (Hämostaseologie, 2019)
Acquired haemophilia A (AHA) is a rare autoimmune disease caused by antibodies directed against clotting factor VIII. About half of cases are idiopathic, but AHA may also be secondary to autoimmune, dermatologic, or oncologic diseases. In approximately 10% of non-idiopathic cases, the disease occurs after or with the diagnosis of cancer as an extremely rare paraneoplastic syndrome. We describe the case of a 73-year-old male patient diagnosed with AHA and successfully treated with recombinant human activated factor VIIa and immunosuppression. Two and a half years later, however, the disease relapsed and a routine ultrasound revealed a liver tumour that was then diagnosed as hepatocellular carcinoma. We present this case to increase awareness that this life-threatening condition may develop years prior to the diagnosis of cancer.
Keywords: acquired haemophilia; hepatocellular carcinoma; haemorrhagic diathesis